(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
The purpose of this article is to discuss fashion exhibitions in art spaces in the city of Rio de Janeiro as a cultural phenomenon, inserted in the unique context of cultural policies in Brazil between 1980 and 2010. In the international scenario, this period corresponds to an effervescence of these events in renowned museums and galleries, arousing the attention of the press and specialized critics around the controversial relationship between luxury companies and artistic institutions. The study of the cases in Brazil delimits the need to consider brazilian economic and political reality that crosses the field of culture. Thus, pointing to particular reconfigurations in the dialogues between art and fashion.